A topical approach to life-span development - Santrock, John W. (New York, NY : McGraw Hill Education, 2023)
"In this new edition, new research and content that has especially been updated and expanded focuses on the following topics: diversity and culture; genetics and epigenetics; neuroscience and the brain; identity issues, especially gender and transgender; health; technology; and successful aging. A Topical Approach to Life-Span Development shows the important connections between the concepts discussed and the real world"--
Includes bibliographical references and index.
Keywords: Developmental psychology